2022
DOI: 10.3390/polym14214516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cellulose Nanofibers’ Structure and Incorporation Route in Waterborne Polyurethane–Urea Based Nanocomposite Inks

Abstract: In order to continue the development of inks valid for cold extrusion 3D printing, waterborne, polyurethane–urea (WBPUU) based inks with cellulose nanofibers (CNF), as a rheological modulator, were prepared by two incorporation methods, ex situ and in situ, in which the CNF were added after and during the synthesis process, respectively. Moreover, in order to improve the affinity of the reinforcement with the matrix, modified CNF was also employed. In the ex situ preparation, interactions between CNFs and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
1
12
0
1
Order By: Relevance
“…In this case, the viscosity of all the siloxane acrylic/CNF nanocomposite latexes were in the range of 214–362 cP. Since the viscosity in polymer latex originates form the interaction between polymer particles and water molecules, such interaction was supposed to be screened by the CNF 38 . Moreover, the lowering of viscosity in nanocomposites might be due to the shear‐thinning during the viscosity analysis 39 .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In this case, the viscosity of all the siloxane acrylic/CNF nanocomposite latexes were in the range of 214–362 cP. Since the viscosity in polymer latex originates form the interaction between polymer particles and water molecules, such interaction was supposed to be screened by the CNF 38 . Moreover, the lowering of viscosity in nanocomposites might be due to the shear‐thinning during the viscosity analysis 39 .…”
Section: Resultsmentioning
confidence: 90%
“…Since the viscosity in polymer latex originates form the interaction between polymer particles and water molecules, such interaction was supposed to be screened by the CNF. 38 Moreover, the lowering of viscosity in nanocomposites might be due to the shear-thinning during the viscosity analysis. 39 Therefore, the ex-situ prepared latex at 0.5 wt% CNF showed much lower viscosity (214 cP) compared to the in-situ latex (362 cP) of same CNF concentration.…”
Section: In-situ Mini-emulsion Polymerization and Exsitu Mixingmentioning
confidence: 99%
“…When inks with poor rheological properties are printed, crushing of the cell wall can take place due to their inability to hold the weight of the top layers . However, this was not the case for the printed composite inks, where, though, elongated pores were observed, there was no trouble in supporting the top layers since no signs of wall crushing could be observed in the micrographies.…”
Section: Resultsmentioning
confidence: 99%
“…Tables 3 and 4 illustrate the work done in the last 2–3 years and clearly highlight the value of NC's distinctive rheological qualities for a wide range of applications. [ 84,120–149 ] Some of the top‐notch characteristics that specifically define the distinctive rheological features of NC suspensions and their ability to act as rheology modifiers in diverse applications include their large water retention/holding potential, remarkable shear thinning behavior, their capabilities to align at high shear rates, thickening impact, and their capacity to form thixotropic frameworks that excellent restoration phenomena. The literature review carried out in the present section makes clear the emerging and cutting‐edge applications of NCs as rheology modulators in the coating [ 117 ] and paint industries [ 118 ] as well as a rheology modulator for cement, [ 119 ] composites, [ 118,120–122 ] electronic devices, [ 122–125 ] cosmetics, foods, [ 117,126–130 ] drilling fluids, [ 122,131 ] and so forth.…”
Section: Advanced Applications Of Nano Cellulose As Rheology Modifiersmentioning
confidence: 99%
“…The superior mechanical, shear thinning, and bio-compatible/non-cytotoxic qualities of NC have also piqued researchers' attention in developing 3D bio-printing materials for creating viable living human organs/tissues. [125,128,[132][133][134][135][136][137][138][139] From the tables, it can be concluded that both CNFs and CNCs have remarkable potential as rheology modifiers/modulators in multiple fields; however, the rapid expansion of such applications at the industrial level is constrained by issues related to their complicated structure and the consistency of production in regards to various features of NC that dramatically influence their rheological behavior.…”
Section: Field Of Application Applicationmentioning
confidence: 99%